Circulating Tumor Cells Expressing Krüppel-Like Factor 8 and Vimentin as Predictors of Poor Prognosis in Pancreatic Cancer Patients. (10th August 2021) - Zhu, Peng; Liu, Hui-Ying; Liu, Fu-Chen; Gu, Fang-Ming; Yuan, Sheng-Xian; Huang, Jian; Pan, Ze-Ya; Wang, Wei-Jun
Background: Circulating tumor cells (CTCs) with an epithelial-mesenchymal transition phenotype in peripheral blood may be a useful marker of carcinomas with poor prognosis. The aim of this study was to determine the prognostic significance of CTCs expressing Krüppel-like factor 8 (KLF8) and vimentin in pancreatic cancer (PC). Methods: CTCs were isolated by immunomagnetic separation from the peripheral blood of 40 PC patients before undergoing surgical resection. Immunocytochemistry was performed to identify KLF8 + and vimentin + CTCs. The associations between CTCs and time to recurrence (TTR), clinicopathologic factors, and survival were assessed. Univariate and multivariate analyzes were performed to identify risk factors. Results: Patients with CTCs ( n = 30) had a higher relapse rate compared to those without ( n = 10) (70.0% vs 20.0%; P < 0.01). The proportion of KLF8 + /vimentin + CTCs to total CTCs was inversely related to TTR ( r = −0.646; P < 0.01); TTR was reduced in patients with > 50% of CTCs identified as KLF8 + /vimentin + ( P < 0.01). Independent risk factors for recurrence were perineural invasion and > 50% KLF8 + /vimentin + CTCs (both P < 0.05). Conclusion: Poor prognosis can be predicted in PC patients when > 50% of CTCs are positive for KLF8 and vimentin.